Aleksei P. Okladnikov : a Biography of a Soviet Archaeologist (1900s - 1950s). - Konopatskii, Aleksander K. (Archaeological Lives Ser., 2019)
Aleksei P. Okladnikov (1908-1981), a prominent Russian archaeologist, spent more than 50 years studying prehistoric sites in various parts of the Soviet Union - in Siberia, Central Asia and Mongolia. This biography will appeal to archaeologists, historians, and anyone interested in the history of the humanities in the twentieth century.